Mechanism of Ca(++)-influx and Ca(++)/Calmodulin-Dependent Protein Kinase IV Activity During In Utero Hypoxia in Cerebral Cortical Neuronal Nuclei of the Guinea Pig Fetus at Term - Vibert, Yanick M. (2008)
Previously we showed that following hypoxia there is an increase in nuclear Ca(++) -influx and Ca(++)/calmodulin-dependent protein kinase IV activity (CaMK IV) in the cerebral cortex of term guinea pig fetus. The present study tests the hypothesis that clonidine administration will prevent hypoxia-induced increased neuronal nuclear Ca(++) -influx and increased CaMK IV activity, by blocking high affinity Ca(++)-ATPase. Studies were conducted in 18 pregnant guinea pigs at term, normoxia (Nx, n=6), hypoxia (Hx, n=6) and clonidine with Hx (Hx+Clo, n=6). The pregnant guinea pig was exposed to a decreased FiO(2) of 0.07 for 60 min. Clonidine, an imidazoline inhibitor of high affinity Ca(++)-ATPase, was administered 12.5µg/kg IP 30 minutes prior to hypoxia. Hypoxia was determined biochemically by ATP and phosphocreatine (PCr) levels. Nuclei were isolated and ATP-dependent (45)Ca(++) -influx was determined. CaMK IV activity was determined by (33)P-incorporation into syntide 2 for 2 min at 37oC in a medium containing 50 mM HEPES (pH 7.5), 2 mM DTT, 40 µM syntide 2, 0.2 mM (33)P-ATP, 10 mM magnesium acetate, 5 µM PKI 5-24, 2 µM PKC 19-36 inhibitor peptides, 1 µM microcystine LR, 200 µM sodium orthovanadate and either 1 mM EGTA (for CaMK IV-independent activity) or 0.8 mM CaCl(2) and 1 mM calmodulin (for total activity). ATP (µmoles/g brain) values were significantly different in the Nx (4.62±0.2), Hx (1.65±0.2, p<0.05 vs Nx), and Hx+Clo (1.92±0.6, p<0.05 vs. Nx). PCr (µmoles/g brain) values in the Nx (3.9±0.1), Hx (1.10±0.3, p<0.05 vs. Nx ), and Hx+Clo (1.14±0.3, p<0.05 vs. Nx). There was a significant difference between nuclear Ca(++)-influx (pmoles/mg protein/min) in Nx (3.98±0.4), Hx (10.38±0.7, p<0.05 vs. Nx), and Hx+Clo (7.35±0.9, p<0.05vs Nx, p<0.05 vs. Hx), and CaM KIV (pmoles/mg protein/min) in Nx (1314.00 ±195.4), Hx (2315.14±148.5, p<0.05 vs. Nx), and Hx+Clo (1686.75±154.3, p<0.05 vs. Nx, p <0.05 vs. Hx). We conclude that the mechanism of hypoxia-induced increased nuclear Ca(++)-influx is mediated by high affinity Ca(++)-ATPase and that CaMK IV activity is nuclear Ca(++)-influx dependent. We speculate that hypoxia-induced alteration of high affinity Ca(++)-ATPase is a key step that triggers nuclear Ca(++)-influx, leading to CREB protein-mediated increased expression of apoptotic proteins and hypoxic neuronal death.